TRADITION OF KIAI KINSHIP AT ISLAMIC BOARDING SCHOOL IN MADURA (Study on Trah, Kiai Kinship, Islamic boarding school in Sumenep) - Mas'odi, Mas'odi (EDUKASIA, 2019)
The purpose of this research is to know deeply about social network of kinship tradition or Trah in Madurese tradition which is defined as "toronan / na’ poto" in which written sequence lineage from a family on kiyai kinship tradition in Madura. Islamic boarding school in Madura average there is still linkage of genealogy or Trah from other islamic boarding school families.The kiyai kinship tradition in some Islamic boarding schools in Madura is closely related to the past of their founders or ancestors who were called "old kiyai" founders of the first Islamic boarding school. The elderly chaplain or founder of islamic boarding school who deliberately matches his grandchildren to another islamic boarding school who is still one family / one of the closest family kiyai is as elderly as the child of his sister, the son of his uncle etc. thus giving birth to new Trah that grow and develop to this day. The method used in this research is Field Research, ie field research conducted in order to collect primary data in the field by using observation, interview and documentation. In addition, this data collection is also equipped with Library Research, which is the use of references in the form of reading books related to research themes to support field dataKeywords: Trah, Patron-Client Social Relations, Kinship